Radiologically induced changes of lipide content in blood plasma, after fractional and prolonged irradiation of laboratorial rats by γ-quantums 60Co - Manouchehr Vatankhah; Y. I. Serkiz (Ядерна фізика та енергетика)
It is discovered that different forms of rat irradiation leads to typical features in dynamic and portioned dependencies of radiogenic changes of lipids content in blood plasma. It is shown that fractional irradiation is more spareful to organism, and prolonged will call significally more radiologically initiated changes, than one-time irradiation. It is set for the first time that on different stages of organism reaction development, examined variables of lipids content, showed different sensitivity to specific doses and forms of irradiation. This testifies that on different stages of organism reaction different components can implement their participation in lipids peroxyding with different speed.